DETEKSI DAN IDENTIFIKASI Austropuccinia psidii PADA MYRTACEAE DI YOGYAKARTA INDONESIA - Istiana Prihatini; I. L. G. Nutjahjaningsih; Farah Aulya Faradilla; Suranto Suranto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2020)
Austropuccinia psidii is a pathogenic fungus that causes rust in the Myrtaceae plant. The extensive plantation of the host of this fungus has increased the attack of fungal pathogen, therefore, will increase the threat to the presence of Myrtaceae species around the globe including in Indonesia. This present study was aiming to detect and identify the presence of this pathogen by morphological and molecular observation. Morphological observation revealed the presence of A. psidii urediniospores on salam (Syzygium polyanthum) and kayu putih (Melaleuca cajuputi) leaves collected from the arboretum of the Indonesian Center for Forest Biotechnology and Tree Improvement (CFBTI), and the presence of teliospores on young Syzygium leaves. PCR amplification using specific primers of Ppsi1 / Ppsi6 succeeded in detecting the presence of A. psidii fungi Melaleuca and Syzygium showed by DNA amplicon length around 500bp. Efforts to obtain ITS DNA sequences to compare the molecular characteristics of fungi from two different hosts have been carried out, however, the sequencing electropherogram was unreadable, so the comparison can not be performed. This study reported that A. psidii is currently present in Myrtaceae species in Yogyakarta, therefore precaution efforts should be conducted to avoid economic and ecological impact from this pathogen.